Residual Immunity from Smallpox Vaccination and Possible Protection from Mpox, China - Yu Huang; Li Guo; Yanan Li; Lili Ren; Jiqin Nie; Fengwen Xu; Tingxuan Huang; Jingchuan Zhong; Zhangling Fan; Yin Zhang; Yu Xie; Qiao Zhang; et al. (Emerging Infectious Diseases, 2024)
Among persons born in China before 1980 and tested for vaccinia virus Tiantan strain (VVT), 28.7% (137/478) had neutralizing antibodies, 71.4% (25/35) had memory B-cell responses, and 65.7% (23/35) had memory T-cell responses to VVT. Because of cross-immunity between the viruses, these findings can help guide mpox vaccination strategies in China.